IMPACT OF THE COVID-19 PANDEMIC ON THE BURNOUT SYNDROME AMONG TEACHERS - Florentin Remus MOGONEA; Florentina MOGONEA (Universitaria Publishing House, Craiova, 2021)
The Covid-19 pandemic represents, at the same time, a global public health problem, as well as a health problem of each individual, including mental and emotional well-being. From the outset, the pandemic generated a general state of alert, at all levels, including education. In most areas of activity, this period has required greater involvement and more sustained efforts to mitigate the disadvantages and risks caused by the pandemic. The current paper aims to examine the impact of the Covid-19 pandemic on the phenomenon of burnout. Has this phenomenon emphasized lockdown and triggered a change in the way of performing the activities? Is there a relationship between the psycho-emotional effects of the pandemic and the burnout syndrome? These are the main questions that we intend to answer, following literature review and an investigation carried out on a sample of pre-service teachers, who participated in a focus-group interview.